2022
DOI: 10.3390/su14169881
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Environmental Conservation Agriculture in Sado Island, Niigata Prefecture, Japan

Abstract: Sado Island in the Niigata prefecture in Japan is one of the first Globally Important Agricultural Heritage Systems (GIAHS) among developed countries and has since been involved in environmental conservation agriculture (ECA). While ECA is still in its early stage in Japan, it has proven to be effective in mitigating climate change in the agricultural sector; hence, this study aimed to identify drivers of ECA among Sado Island paddy farmers. The data revealed the prevalence of farmers’ cognitive dissonance bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Farmers in developed countries were concerned about CC and its impact on their farm yield. Hence, they understand the importance of adaptation and mitigation strategies (Maharjan, Gonzalvo and Aala, 2022a; Mohring, Finger and Dalhaus, 2022; Roesch-McNally, Garrett and Fery, 2020). Some farmers perceived these importances to shift to environmental-friendly practices (Maharjan, Gonzalvo and Aala, 2022a; Mohring, Finger and Dalhaus, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Farmers in developed countries were concerned about CC and its impact on their farm yield. Hence, they understand the importance of adaptation and mitigation strategies (Maharjan, Gonzalvo and Aala, 2022a; Mohring, Finger and Dalhaus, 2022; Roesch-McNally, Garrett and Fery, 2020). Some farmers perceived these importances to shift to environmental-friendly practices (Maharjan, Gonzalvo and Aala, 2022a; Mohring, Finger and Dalhaus, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In Japan, a study found that some farmers perceived environmental conservation agriculture (ECA) as a strategy to mitigate CC. Limiting the use of pesticides or chemical substances will benefit the environment, according to participants with high concerns about biodiversity and ecological resources (Maharjan, Gonzalvo and Aala, 2022a). In another study, Maharjan, Gonzalvo and Aala (2022b) found that ECA has allowed Japanese farmers to earn higher profits by direct selling to consumers.…”
Section: Farmers In Developed Countriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of understanding of how environmental conservation agriculture (ECA) translates into climate change activism limits farmers' aspirations to improve their local/global environment and boost their production. Additionally, there is a heterogeneity of factors influencing some farming communities in terms of effective adoption techniques for ECA [6].…”
Section: Introductionmentioning
confidence: 99%